The Dynamic Impact of High Oil Price Shock on the Algerian Economy: An Econometric Study during the Period (1980-2018) Using the SVECM Model - قدال, زين الدين; موسي, آسية (Finance and Business Economies Review, 2021)
This study investigates the effect of high oil price shock on the Algerian economy, during the period (1980-2018) using the structural vector error correction model. The results of the Johansen test indicate the existing of a long-run equilibrium relationship between the study variables, The impulse response function (IRF) showed that the structural oil price shock is great and positively affects the GDP per capita and negatively effects the unemployment rate and the exchange rate in the short and long term, as for the inflation rate response it was negative in the short run, so it became positive in the long run. the results of the variance decomposition revealed that the oil price explains most of the changes that occur in unemployment rate and the GDP per capita, as well as the weak percentage of the changes that happen in both inflation rate and exchange rate in the short and long term.